Proservice or antiservice employee behaviors: A multilevel ethics perspective. Issue 5 (20th October 2017) - Kao, Feng-Hsia; Cheng, Bor-Shiuan
ABSTRACT: We adopt a multilevel approach to investigate ethical ideology, moral leadership, and ethical climate in predicting service-oriented organizational citizenship behavior (OCB) and service sabotage. Data were collected from 36 food and beverage units in hotels in Taiwan. The sample comprised 504 employees and 36 supervisors. Results show that idealism is positively related with service-oriented OCB, but negatively related with service sabotage; relativism is the opposite. Moral leadership and ethical climate are both positively related with service-oriented OCB and negatively related with service sabotage. In addition, moral leadership moderates the relationship between relativism and service-oriented OCB. Ethical climate moderates the relationship between idealism and service-oriented OCB and service sabotage. The implications of this study for research and practice are discussed.